Michel Foucault y la dirección espiritual en los textos patrísticos - Peretá Rivas, Rubén (Augustinianum, 2025)
The aim of this article is to analyse Michel Foucault's reflections in his later writings (from 1979 onwards) on the subject of spiritual direction and its relationship to penance as treated by some Church Fathers, particularly Cassian and Tertullian. Foucault explored these patristic texts with the aim of developing a genealogy of the subjectivation of Western man, focusing on the duty of verdicition or "telling the truth" about oneself. According to the author, these are "technologies" with which, through self-manifestation or exomologesis, "the subject is constituted" in Christianity, which is closely related to the practice of confession and spiritual direction. After an exposition of the fundamental points of Foucault's theory, an assessment of his assertions will be made from the point of view of patrology. In particular, the methodological limitations of his reading will be pointed out, which does not take into account various factors and elements essential for a well-founded study, which, on occasion, invalidates his conclusions.